Connecting New Trends and New Skills for Academic Librarians - Sanches, Tatiana (2022)
Guiding documents of professional associations are revealing the main future trends around the globe in information science. This study seeks to systematize and identify the skills expressed in them and aimed at information professionals. Thus, the content of the guiding documents is analyzed to find the trends for the area, systematizing them in areas of interest. The skills needed by the professionals that emanate from it are identified. In addition, a survey of future professionals (graduate students) is carried out to try to understand what skills are valued in the future performance of their profession. It is noted that it is important to be aware of current trends and recommendations for the sector. Therefore, the preparation of students in information science for the prospects for the future will be more appropriate and meaningful, bringing benefits to themselves and to the academic communities in which they operate, if future librarians in higher education become aware of a changing world in which they will have to act.